The effectiveness of galangal Alpinia galanga extract for the treatment of sangkuriang catfish Clarias gariepinus infected Aeromonas hydrophila - Andriani, Yuli; Setyo Wati, Desy; Zidni, Irfan; Grandiosa Herman, Roffi (Indonesian Society of Scientific Aquaculture (ISSA), 2024)
The purpose of this research is to find out the optimal dose of galangal extract to treatment of Sangkuriang catfish infected with Aeromonas hydrophila, the fish fry used are 5-7 cm in size. October-November 2022 was the research was carried out by an experimental method using a completely randomized design (CRD) with four treatments and three replications. The treatment used was immersing with galangal extract for 24 hours with doses of 0 mg/L (A), 250 mg/L (B), 500 mg/L (C) and 750 mg/L (D). Maintenance of test fish for 14 days. Aeromonas hydrophila bacteria are used to infect fish with a density of 108 CFU/ml by immersing 10 ml in 10 liters of water. Clinical symptoms of infection, clinical symptoms of recovery period, survival rate and water quality were used as parameters in this research. The results showed that the use of galangal extract for treatment of Sangkuriang catfish fry infected with Aeromonas hydrophila by immersion method for 24 hours at a concentration of 500 mg/L was the best treatment with the survival rate of 90%. Keywords: Aeromonas hydrophila, Sangkuriang catfish fry, galangal extract ABSTRAK Riset ini bertujuan untuk menentukan dosis optimum ekstrak lengkuas untuk mengobati ikan lele sangkuriang yang terinfeksi Aeromonas hydrophila, benih ikan yang digunakan berukuran 5-7 cm. Oktober-November 2022 adalah waktu penelitian dilaksanakan. Metode eksperimen yang digunakan dalam penelitian ini adalah Rancangan Acak Lengkap (RAL) yang menggunakan empat perlakuan serta tiga ulangan. Perlakuan yang digunakan adalah perendaman dengan ekstrak lengkuas selama 24 jam dengan dosis masing-masing 0 mg/L (A), 250 mg/L (B), 500 mg/L (C) dan 750 mg/L (D). Pemeliharaan ikan uji selama 14 hari. Bakteri Aeromonas hydrophila digunakan untuk menginfeksi ikan dengan kepadatan 108 CFU/ml dengan cara merendam 10 ml dalam 10 liter air. Parameter yang diamati meliputi gejala klinis penginfeksian, gejala klinis masa pemulihan, kelangsungan hidup dan kualitas air. Hasil riset menunjukkan bahwa penggunaan ekstrak lengkuas untuk mengobati benih ikan lele sangkuriang yang terinfeksi Aeromonas hydrophila dengan metode perendaman selama 24 jam pada konsentrasi 500 mg/L merupakan perlakuan terbaik dengan kelangsungan hidup sebesar 90%. Kata kunci: Aeromonas hydrophila, benih ikan lele sangkuriang, ekstrak lengkuas